A Comparative Review of Communication Technologies for Asset Tracking in Healthcare Facilities - Al-Maktary, Omar; Susanto, Misfa (Applied Engineering, Innovation, and Technology, 2025)
Efficient asset tracking in healthcare facilities is essential to reduce delays, prevent equipment loss, and optimize operational workflows. This study systematically reviews four widely used technologies: Radio Frequency Identification (RFID), Near Field Communication (NFC), Global Positioning System (GPS), and Bluetooth Low Energy (BLE), based on six criteria: cost, accuracy, range, energy efficiency, ease of deployment, and scalability. RFID and NFC offer high accuracy in short-range use cases, but RFID requires substantial infrastructure, while NFC is limited by its manual operation. GPS is highly effective for outdoor tracking, though it struggles indoors. BLE provides a strong balance across all criteria and supports long battery life, making it suitable for large-scale indoor tracking. The review incorporates real-world case studies and proposes hybrid IoT-based systems that combine these technologies to achieve comprehensive coverage. Future research should focus on seamless indoor-outdoor handoff, energy-efficient synchronization, and the use of machine learning for signal optimization.